Sequential occurrence of IgM, IgM/IgG, and gp120-IgM/IgG complement complexes on CD4+ lymphocytes in relation to CD4+ blood lymphocyte depletion in HIV+ hemophilia patients: results of a 10-year study - Daniel, Volker; Süsal, Caner; Weimer, Rolf; Zipperle, Silvia; Kröpelin, Marianne; Zimmermann, Rainer Johannes; Huth-Kühne, Angela; Opelz, Gerhard (Immunology letters, 1995)
The concept of autoimmune mechanisms playing an integral role in the pathogenesis of HIV disease is rapidly gaining ground. In this study, we determined IgM and IgG antibodies, complement fragments and gp120 on the surface of CD4+ lymphocytes using double-fluorescence flow cytometry. Sequential analysis demonstrated an inverse relationship of autoantibodies and CD4+ lymphocyte counts in the peripheral blood. HIV+ patients without autoantibodies (16104 = 15%) had the highest CD4+ blood cell counts (324 ± 264/μl; mean ± SD). CD4+ counts were successively lower in patients with complement-fixing IgM (243 ± 240/μl), complement-fixing IgG and IgM (139 ± 138/μl), or gp120-IgM/IgG complement complexes on the surface of CD4+ cells (38 ± 45/μl, P = 0.03). Individual patient profiles show that IgM autoantibodies typically are formed early after HIV infection and appear to deplete CD4+ lymphocytes very slowly, whereas complement-fixing IgG autoantibodies are generated at a later stage and deplete CD4+ lymphocytes more efficiently. The presence of both soluble gp120 and complement-fixing autoantibodies on CD4+ lymphocytes is associated with very low CD4+ cell counts and coincides with progression to terminal disease. Early during HIV infection autoantibody production is rather unstable, but it becomes more stable with disease progression and persists in advanced stages of the disease. These data suggest that autoantibody formation against CD4+ lymphocytes is a pathogenic mechanism for CD4+ cell depletion.